Investigating Speaking Anxiety in Indonesian Young Learner Classrooms: A Qualitative Descriptive Study - Agustin, Aditya Galih; Sulistyo, Teguh; Sholeh, Agus (Journal of Language and Literature Studies, 2025)
Language anxiety among learners, especially young learners, can be alarming, and it is estimated that up to one-half of all language students experience debilitating levels of speaking anxiety. Students’ anxiety can influence both the fluency and the accuracy of speaking because anxiety acts as a distraction. Therefore, being aware of students’ speaking anxiety is important. This study aimed to analyze the students’ speaking anxiety in a young learner classroom. The study employed a descriptive qualitative design. This study was conducted with a sample of 35 students. Two instruments were used in this study, which included: observation, a questionnaire, and an interview. The process of data analysis included data condensation, data display, and conclusion drawing and verification. The data gathered were then verified by an expert validator. The result of this study indicated that the majority of students had a high level of anxiety in the anxious category. This result certainly deserved attention in the implementation of the speaking learning process because it was possible for anxiety to contribute to students' speaking failure. Furthermore, there were a number of factors that contributed to the speaking anxiety faced by students with high and low anxiety. These factors were generally related to internal and external factors. In terms of internal factors, the students were worried about their language skills, afraid of making mistakes when speaking English, and had low confidence. In terms of external factors, the students were afraid of getting bad grades, afraid of being laughed at by their friends, afraid of getting negative feedback from the teacher, and afraid that their English would not be understood. In addition, both students with high and low anxiety had a number of strategies to reduce speaking anxiety. Those strategies were included: preparing, practicing, relaxing, smiling, taking a deep breath, making jokes, and looking away in various directions during the speaking performance. The implications and suggestions of the research are also discussed.